Strategy Formulation and Financial Performance Perceptions and Relationships. The Mediating Role of Strategic Approaches.: Array - Mashingaidze, Mugove; Chinakidzwa, More (The Journal of Accounting and Management, 2021)
The study investigated the relationship between strategy formulation and financial performance perceptions of manufacturing SMEs in Zimbabwe. The study further examined the mediating role of strategic approaches on the relationship between strategy formulation and financial performance in the SMEs. A quantitative study of 368 SMEs was done in Harare, Zimbabwe using a self-administered questionnaire. Structural Equation Modelling (SEM) was performed to test the research hypotheses. Results indicate that the key activities of strategy formulation as stipulated by literature are somewhat observed among manufacturing SMEs in Zimbabwe. The results showed a statistically significant influence of strategy formulation on both short-term and long-term financial performance perceptions. However, the study established a non-statistically significant mediation relationship between strategy formulation and financial performance via both the prescriptive and the descriptive approaches. Despite this study’s importance, the current study results could be biased because the mediation effect was tested using cross-sectional data. A longitudinal survey would be ideal for testing the strategic approaches’ mediation effect.